2014
DOI: 10.1021/jf405507e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of aPoria cocosProtein That Activates Th1 Immune Response and Allays Th2 Cytokine and IgE Production in a Murine Atopic Dermatitis Model

Abstract: Edible fungus Poria cocos (Schw.) Wolf is a cooking material that has myriad health benefits. However, its active constituents have not been well-defined. We previously purified an immunomodulatory protein, PCP, from P. cocos and described its biochemical features and its ability to activate primary macrophage via TLR4. In this study, we cloned the gene of PCP and demonstrated its ability to activate Th1 response in cell cultures and in mice. The complete cDNA sequence of PCP consisted of 807 bp, which include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The P.cocos is widely used as a traditional medicine in treatment of Jaundice. It extract has beneficial effects on inflammation, cancer and immune function [8][9][10][11]. The combination of P.cocos and western drug for patients with Jaundice also receive a good therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The P.cocos is widely used as a traditional medicine in treatment of Jaundice. It extract has beneficial effects on inflammation, cancer and immune function [8][9][10][11]. The combination of P.cocos and western drug for patients with Jaundice also receive a good therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…PCP stimulated mouse peritoneal macrophages (RAW264.7) by interacting with toll-like receptor 4 and subsequently activating the NFκB signaling pathway. Oral administration of PCP reduced the production of serum total IgG1 and OVA-specific IgG1 and upregulated the serum OVA-specific IgG2a and splenic Th1-related cytokine and downregulated IL-4 and IgE levels in atopic dermatitis mice [74]. P. antler tray proteins (PSAB) is a mixture of 5 proteins with a molecular mass of 10 to 70 kDa and includes 17 amino acids.…”
Section: Biological Activities Of Biomacromolecules Based On Its Effimentioning
confidence: 99%
“…Originally, its sclerotium has been used as an important medicinal herb in several Asian countries, particularly China, Japan and Korea, for its sedative, diuretic, anti-depressant and tonic activities (9,10). Recent studies have indicated that the extracts and components of this fungus display a variety of biological activities, such as anti-fungal and anti-bacterial (11), anti-oxidant (12,13), neuroprotective (14), anti-hypertonic (15), anti-inflammatory (16)(17)(18)(19), anti-angiogenic (20,21), immunomodulatory (22,23) and anticancer effects (24,25). Although several triterpenoids from P. cocos have been isolated and were demonstrated to have a cytotoxic effect against a number of human cancer cell types (26)(27)(28)(29), the efficacy and mechanism of the whole extract in cancer treatment have not been systemically evaluated.…”
Section: Introductionmentioning
confidence: 99%